Tanggung Jawab Sosial serta Kemanusiaan Masyarakat Buddhis - Alberto Ardiansyah, Alberd; Astuti, Dewi; Dewi, Muditya Ratna (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2025)
This research explores the role of social and humanitarian responsibility within Buddhist teachings, focusing on the application of the concepts of loving-kindness (metta), compassion (karuna), and virtue (kusala) in daily life. The central question addressed is how Buddhist teachings encourage the social involvement of its followers in alleviating suffering and improving social conditions. The aim of this research is to understand the impact of Buddhist social responsibility on the behavior of its followers and social welfare. The method used is a Systematic Literature Review (SLR) and literature review, analyzing research and literature related to Buddhist social responsibility from online databases such as Google Scholar and Portal Garuda. The results of the research indicate that social responsibility in Buddhism involves philanthropy and inner purification, with social activities such as charity and community projects serving as manifestations of the Dhamma teachings. The Buddhist Economic concept emphasizes both material and spiritual well-being. In conclusion, Buddhist teachings play a significant role in shaping social engagement that has a positive impact on the well-being of individuals and society.